Long-Term Trends of Northern Bobwhite Populations and Hunting Success on Private Shooting Plantations in Northern Florida and Southern Georgia - Leonard A. Brennan; Jeffrey M. Lee; R. Shane Fuller (National Quail Symposium Proceedings, 2017)
Nearly all broad-scale assessments (U.S. Department of the Interior, Fish and Wildlife Service [USDI-FWS], Breeding Bird Surveys, Audubon Society Christmas Bird Counts, and state game agency harvest surveys) of northern bobwhite (Colinus virginianus) population trends during the past 30 to 50 years point to widespread declines at local, regional and national scales. Long-term records of populations that do not show long-term bobwhite declines are rare. Landowners and managers in the shooting plantation country between Tallahassee, Florida and Thomasville, Georgia have been recording quail hunting and bag records for many years. Such information can provide valuable insight into the long-term trends of bobwhite populations. We therefore analyzed bag records from 5 different properties where data had been collected for periods ranging from 14 to 80+ years. Trends from these data were completely opposite from long-term trends shown from other sources such as Breeding Bird Survey and Christmas Bird Count data. These data indicate that a long-term, continuous approach to habitat management (primarily burning with prescribed fire, and frequent soil disturbance from disking) can sustain abundant bobwhite populations and high-quality shooting. These data also call into question alternative hypotheses such as invasion of the red imported fire ant and range expansion of the coyote as being responsible for the long-term bobwhite decline. Both fire ants and coyotes are common in the Thomasville-Tallahassee area, yet, abundant bobwhite populations persist, presumably as a function of high-quality habitat management.